A política da promoção da saúde de Belo Horizonte: avanços e desafios - Tammy Angelina Mendonça Claret Monteiro (2017)
This work aims the study of health promotion policy and to reflect on the importance of its institutionalization within intersectoral programs and practices. Starting from the historical survey of this movement, which goes back to the 1974 Lalonde report, we will go foward to describe its theoretical foundations (literature review) in the context of the discussions for an egalitarian social policy based on the principles of solidarity, equality and efficiency, comparing them with The political-institutional frameworks of Brazilian Public Policies on Health Promotion, at the federal level, in the State of Minas Gerais and in the municipality of Belo Horizonte. Finally, we report our experience in the Ambulatory / Network for the Promotion of Women's Health in Situations of Violence and Vulnerability, put into practice by the Faculty of Medicine and the Hospital das Clínicas of Federal University of Minas Gerais, in partnership with Belo Horizonte Town Secretary - SUS - BH and with the Family Citizen Program.